2017
DOI: 10.1155/2017/6593073
|View full text |Cite
|
Sign up to set email alerts
|

Spondias purpurea L. (Anacardiaceae): Antioxidant and Antiulcer Activities of the Leaf Hexane Extract

Abstract: Spondias purpurea is used in folk medicine to treat diarrhea and diuresis. The objective of this study was to evaluate the phytochemical profile and antioxidant and antiulcer activities of the hexane extract of the leaves of S. purpurea (SpHE). Phytochemical profile was evaluated via thin layer chromatography (TLC) and HPLC. SpHE was screened for antioxidant activities using DPPH, ABTS, FRAP, and phosphomolybdenum assays. To determine its antiulcer properties, animals were pretreated with injured control, lans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 60 publications
(69 reference statements)
1
19
0
6
Order By: Relevance
“…Both PGE 2 and TNF-α can be controlled by TLR-2/ MyD88 signaling pathway, and numerous studies have demonstrated that downregulation of TLR-2/MyD88 signaling pathway [37], promotion of PGE 2 secretion [4], and inhibition of TNF-α expression [3,5] could make important contribution to the suppression of the development of peptic ulcer. In the present study, we observed the marked upregulation of TLR-2, MyD88, and TNF-α in the epithelium and the granulation tissues at the base of the ulcer, compared with normal duodenal tissues without ulcers, which implied that these factors could accelerate ulcer formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both PGE 2 and TNF-α can be controlled by TLR-2/ MyD88 signaling pathway, and numerous studies have demonstrated that downregulation of TLR-2/MyD88 signaling pathway [37], promotion of PGE 2 secretion [4], and inhibition of TNF-α expression [3,5] could make important contribution to the suppression of the development of peptic ulcer. In the present study, we observed the marked upregulation of TLR-2, MyD88, and TNF-α in the epithelium and the granulation tissues at the base of the ulcer, compared with normal duodenal tissues without ulcers, which implied that these factors could accelerate ulcer formation.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term treatment with H 2 RA may lead to the development of undesirable effects such as osteoporosis, galactorrhea, gynecomastia, and alteration of the bacterial flora of the gastrointestinal tract. Furthermore, PPIs and H 2 RAs can induce rapid tolerance during therapeutic process and rebound of hyper gastric acid secretion following withdrawal of drugs, which leads to high recurrence rate of ulcers [3].…”
Section: Introductionmentioning
confidence: 99%
“…These lesions affect about four million people worldwide, more often men than women, with duodenal ulcer more prevalent among young people and gastric ulcer among the elderly [ 1 , 3 ]. Currently, treatment options for peptic ulcer are based on the use of antacids, cytoprotective agents, muscarinic antagonists, H 2 antihistamines, proton pump inhibitors, and more recently the use of antimicrobials for the treatment of Helicobacter pylori infection [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…A literatura científica traz ainda a presença de outras classes de compostos como fenóis e seus derivados, dentre eles a epigalocatequina e os ácidos elágico, clorogênico e caféico, bem como derivados do ácido cinâmico. Estes compostos, além de possuírem importantes propriedades antioxidantes, provavelmente são os responsáveis pelo potencial anti-inflamatório das espécies desta família botânica frente enfermidades inflamatórias (ALMEIDA et al, 2017;CABRAL et al, 2016;CARVALHO et al, 2013;ROSAS et al, 2015).…”
Section: Resultsunclassified
“…No mesmo sentido, a atividade anti-inflamatória de taninos está vinculada à sua capacidade de inibição na produção ou ativação de mediadores pró-inflamatórios, além de inibir a quimiotaxia de leucócitos (AMBRIZ-PÉREZ et al, 2016;BREZANI et al, 2018). As saponinas, por sua vez, exibem ação anti-inflamatória associada aos mecanismos de supressão das vias de sinalização de NF-κB, fosfoinositida 3-quinase e de proteína quinase ativada por mitógeno (JANG et al, 2013).…”
Section: Resultsunclassified